Organizational I Mathematical and Statistical Analysis Pedagogical Experimental Work Detail Preschool Education Organization 5-7 Years - Salimov Gairat Mukhamedovich (Zien Journals, 2025)
This article defines the criteria for assessing the physical fitness of preschool children; determining the results of an experiment among preschoolers using mathematical and statistical methods. Research stages, research methods, analysis of scientific literature sources, the effectiveness of the proposed methodology in pedagogical research, which is confirmed by a mutual comparison of indicators recorded based on the results of the experimental work, and advanced mathematical and statistical methods of reanalysis. results
Keywords: research; method; physical training